the limit 25

Calculus Level 2

lim n 2 n + ( 1 ) n 2 n + 1 + ( 1 ) n + 1 = ? \lim_{n \to \infty} \frac {2^n + (-1)^n}{2^{n+1}+(-1)^{n+1}} = \ ?


The answer is 0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

lim n 2 n + ( 1 ) n 2 n + 1 + ( 1 ) n + 1 = lim n 1 + ( 1 2 ) n 2 ( 1 2 ) n = 1 2 \lim_{n\rightarrow∞ } \frac{2^n +(-1)^n}{2^{n+1}+(-1)^{n+1}}=\lim_{n\rightarrow∞}\frac{1+(-\frac{1}{2})^n}{2-(\frac{1}{2})^n}= \frac{1}{2}

There is a typo lim n \lim_{n\to\infty}

Hana Wehbi - 4 months, 4 weeks ago

why is it 2 - (1/2)^n instead of 2 - (-1/2)^n ?

Mohamed Sobhy - 4 months, 1 week ago

(-1)^n is ±1 2^n ± 1 = O(2^n) 2^{n+1} ± 1 = O(2^{n+1}) Therefore the limit is 2^n / 2^{n+1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...